Analysis of Antibiotic Use in COVID-19 Patients at a Hospital in Sidoarjo - Weni Kristanti; Rika Yulia; Fauna Herawati (Jurnal Farmasi dan Ilmu Kefarmasian Indonesia)
Background: Antibiotics are given to COVID-19 patients to treat bacterial co-infections, but excessive and inappropriate antibiotic use can increase antibiotic resistance. Objective: The study aims to analyze the antibiotic use and bacterial susceptibility in COVID-19 patients at a hospital in Sidoarjo - East Java. Method: The research design used was a prospective cross-sectional study using data collection of sputum culture, bacterial susceptibility, medical records, and Pharmacy antibiotics usage from August to October 2021. The Research sample is moderate-to-severe COVID-19 patients. Result: The results showed that in August-October 2021, 32 patients met the study sample category, where the most were men (56.25%), age range 46-55 years (31.25%), and outcome recovered as much as 81.25%. The culture results showed that only 1 (one) person out of 32 samples had bacterial growth. The only bacteria that grew in the sputum culture was Enterobacter aerogenes, susceptible to meropenem but resistant to levofloxacin. The highest quantity of antibiotics in this study was levofloxacin 71,16; meropenem 32.25; moxifloxacin 21.84 DDD/ 100 bed days. Conclusions: Most of the cases of COVID-19 occurred in men; the age range was 46-55 years, and the outcome recovered was more than those who died. Bacterial co-infection occurred in 3.12% of patients who received meropenem and levofloxacin during their hospitalization. The largest quantity of antibiotics used was levofloxacin, meropenem, and moxifloxacin. The combination of meropenem and levofloxacin should be re-evaluated because levofloxacin is resistant but still susceptible to meropenem.